Cross-Cultural Variation in the Full Translation of The Peony Pavilion - Xiaorong, Zheng; Liu, Liu (Sinología hispánica. China Studies Review, 2026)
Mudan ting (The Peony Pavilion) is a classic play written between 1593 and 1598 by the eminent Chinese playwright Tang Xianzu (1550-1616). During the 20th century, the play was translated into numerous foreign languages, including German, French, and English. Its first complete Spanish translation, by Professor Alicia Relinque Eleta, was published in 2016 to commemorate the 400th anniversary of Tang Xianzu’s death. This analysis aims to study textual variations in the Spanish translation by comparing it with the original Chinese work, examining the process of variation, analyzing its causes and exploring cultural differences, with the purpose of demonstrating that translation is not a mechanical conversion of language, but a recreation of the translator based on the translator’s own social and historical environment, cultural traditions and the actual needs of the receiving country.